(untitled) (Groundings Undergraduate, 2024)
This research paper delves into the contrasting interpretations of the muse by Mary Wollstonecraft and William Wordsworth, as evidenced in their seminal works A Vindication of the Rights of Woman and the Preface to Lyrical Ballads, respectively. The paper critically evaluates how each interpretation shapes contrasting truths about the production and consumption of literature. Wollstonecraft, advocating for reason as her muse, challenges societal norms and seeks to empower women through education. In contrast, Wordsworth embraces feeling as his muse, aiming to directly communicate with the heart of his reader. Through a comparative analysis, this paper explores how these distinct muses inform the authors’ approaches to subjects such as education, uniformity, and gender. Furthermore, it examines the Rousseauvian influences on their views, and how each author’s position of power shapes their narrative. Ultimately, it highlights the radical nature of both texts in the democratisation of poetry and the elevation of the female sex.